Revenue Management and the Rise of the Algorithmic Economy - Lobel, Ilan (Management Science, 2021)
Revenue management has evolved over the years from its origins in the airline industry into a much broader discipline that analyzes algorithmic methods for demand and marketplace management, but many outside of the discipline are not aware of this transformation. The field’s transition tracks the widespread adoption of algorithmic decision-making techniques by businesses in a wide variety of industries over the last decade. We study this evolution in the field’s breadth of research, with a particular focus on revenue-management papers that study online marketplaces such as e-commerce retailing, digital advertisement, and ride-hailing markets for urban transportation. This paper was accepted by David Simchi-Levi, Special Section of Management Science: 65th Anniversary.